161k views
1 vote
If f(x)=x^2 and g(x)=1/2x+3 find g(f(-1))

If f(x)=x^2 and g(x)=1/2x+3 find g(f(-1))-example-1

2 Answers

1 vote
g
(
f
(
x
)
)
g
(
f
(
x
)
)
Evaluate
g
(
f
(
x
)
)
g
(
f
(
x
)
)
by substituting in the value of
f
f
into
g
g
.
g
(
2
x

3
)
=
(
2
x

3
)
+
1
g
(
2
x
-
3
)
=
(
2
x
-
3
)
+
1
Add

3
-
3
and
1
1
.
g
(
2
x

3
)
=
2
x

2
User Cody Parker
by
5.6k points
3 votes

Answer:

1/5

Explanation:

F(x)=x^2

g(x)=1/(2x+3)

g(f(-1))=?

x=-1→f(-1)=(-1)^2→f(-1)=1

g(f(-1))=g(1)=1/[2(1)+3]=1/(2+3)→g(f(-1))=1/5

User Jrisberg
by
5.1k points